Reforging the Iron Cross : the search for tradition in the West German armed forces - Abenheim, Donald, 1953- (Princeton legacy library, 1988)
Recent controversies about Ronald Reagan's visit to the Bitburg military cemetery and revelations about Kurt Waldheim's past underscored the political problems inherent in Germany's military traditions and in the relationship of the army to National Socialism. The Allied victors disbanded the German armed forces after World War II, only to press for the arming of the Federal Republic of Germany under the altered political conditions of the cold war. This book is the first comprehensive narrative and analysis of the efforts of German military professionals to discover for their new army an acceptable body of tradition in the proud, ambiguous, and at times criminal history of the German soldier. The author shows that, despite a complex of political obstacles, the founders of the Bundeswehr generally succeeded in persuading the international community and Germany itself that the army of the 1950s and 1960s would not revive the militarism of the past. However, the rapidity of the military buildup was a major drawback to their reform ideas. Certain officers and NCOs in the Bundeswehr undercut changes made by the leadership, and the debate on tradition building became a major political issue in the Federal Republic and NATO. Originally published in 1989. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.